CircRNAs in the brain. Issue 8 (3rd August 2017) - Hanan, Mor; Soreq, Hermona; Kadener, Sebastian
ABSTRACT: Circular RNAs (circRNAs) are highly abundant and evolutionarily conserved non-coding RNAs produced by circularization of specific exons. Since their re-discovery as potential regulators of gene expression, thousands of circRNAs were detected in different tissues and cell types across most organisms. Accumulating data suggest key roles for them in the central nervous system. Neuronal-expressed RNAs are diverted to yield highly enriched CircRNAs in human, mouse, pig and flies, with many of them enriched in neuronal tissues. CircRNA levels are dynamically modulated in neurons, both during differentiation and following bursts of electrical activity, and accumulate with age, and many of them are enriched in synapses. Together, available data suggest that circRNAs have important roles in synaptic plasticity and neuronal function. This review covers current advances in the field and lays out hypotheses regarding functions of circRNAs in the brain as well as their putative involvement in initiation and progression of neurodegenerative processes.